Off-Court Generic Perceptual-Cognitive Training in Elite Volleyball Athletes: Task-Specific Effects and Levels of Transfer - Fleddermann, Marie-Therese; Heppe, Holger; Zentgraf, Karen (Frontiers in Psychology, 2019)
Background: The nature of perceptual-cognitive expertise in interactive sports has gained more and more scientific interest over the last two decades. Research to understand how this expertise can be developed has not been addressed profoundly yet. In approaches to study this with interventional designs, only few studies have scrutinized several levels of transfer such as to the field. Therefore, the aim of this study was to examine the efficacy of a generic off-court perceptual-cognitive training in elite volleyball players on three different levels: task-specific, near-transfer, and far-transfer effects. Based on overlapping cognitive processes between training and testing, we hypothesized task-specific improvements as well as positive near- and far-transfer effects after a multiple-object tracking training intervention. Methods: Twenty-two volleyball experts completed a 8-week three-dimensional (3D) multiple-object tracking (3D-MOT) training intervention. A control group (n = 21; volleyball experts also) participated in regular ball practice only. Before and after training, both groups performed tests on the 3D-MOT, four near-transfer tests in cognitive domains, and a far-transfer, lab-based, and volleyball-specific blocking test. Results: The results of the 2 × 2 analysis of variance (ANOVA) (group, time) showed significant interaction effects in the 3D-MOT task [F(1,40) = 93.10; p < 0.001; ηp2 = 0.70] and in two near-transfer tests [sustained attention: F(1,40) = 15.45; p < 0.001; ηp2 = 0.28; processing speed: F(1,40) = 12.15; p = 0.001; ηp2 = 0.23]. No significant interaction effects were found in the far-transfer volleyball test. Conclusions: Our study suggests positive effects in task-specific and two near-transfer tests of a perceptual-cognitive intervention in elite volleyball athletes. This supports a partial overlap in cognitive processing between practice and tests with the result of positive near-transfer. However, there are no significant effects in far-transfer testing. Although these current results are promising, it is still unclear how far-transfer effects of a generic perceptual-cognitive training intervention can be assured.